Genda - Farooqui, Fauzia Ihsan (Karachi : Qxford university press, 2019)
"Urdu Ka Guldasta: Gainda" is a Class 2 Urdu language textbook authored by Fozia Ahsan Farooqui and published by Oxford University Press. This special edition, known as Khususi Isha$1 (Bat, is aligned with Pakistan$1 (Bs Single National Curriculum (SNC) 2020, aiming to enhance student engagement and learning outcomes.s
Genda is a beautifully illustrated Urdu picture book that tells the heartwarming story of a little elephant named Genda. The narrative follows Genda$1 (Bs adventures and misadventures in the jungle, focusing on themes of friendship, curiosity, and learning from mistakes. The story is designed to engage young readers through simple yet expressive language and vivid artwork that brings the jungle and its characters to life.s
Shelving location
Genda is a beautifully illustrated Urdu storybook suitable for early primary school students, particularly those in Kindergarten to Grade 2. With its simple yet engaging language, vibrant visuals, and relatable characters, the book is ideal for young readers who are beginning to develop fluency in Urdu. It is especially beneficial for children aged 4 to 7 years, helping them build vocabulary, comprehension skills, and a love for storytelling. The book can be used effectively in Urdu language classes, library read-aloud sessions, and integrated story-based learning activities.
Keywords: Urdu - Text Book; Oxford - Urdu text book